PENERAPAN POLA PBMP DAN MODEL PEMBELAJARAN JIGSAW UNTUK MENINGKATKAN KETUNTASAN BELAJAR PADA MATERI KIMIA KARBON SISWA KELAS XII-IPA-2 SMAN 6 MADIUN SEMESTER 2 TAHUN PELAJARAN 2014-2015 - Sumarni, Tintin Dwi (Jurnal Penelitian LPPM (Lembaga Penelitian dan Pengabdian kepada Masyarakat) IKIP PGRI MADIUN, 2016)
This study aims to determine the participation and motivation of the students, student learning outcomes and determine the quality of chemistry by combining Jigsaw model and PBMPpatterns on the material of Carbon Chemistry. This study is a Classroom Action Research held on two cycles. The subjects of this study were the students of class XII-IPA-2 SMAN 6 Madiun in the Academic Year 2014-2015. The research design uses Classroom Action Research with two cycles, where each round consists of plans, activities and observation, reflection and revision of the draft. The methods of data collection is test data results, student activity sheets observation and datamanagement of learning. While the devices used are the Lesson Plan, Hand Out, and the Student Worksheet. Data were analyzed descriptively. The results achieved in this study are: 1) The score of each test cycle shows that the application of a PBMP and Jigsaw model can improve studentsmastery learning. In the first cycle, the percentage of classical completeness is 70.59%. In the second cycle, the percentage of classical completeness is 85.29%. 2) The response of students in applying PBMP patterns and Jigsaw model in the learning process carbon chemistry provides positive feedback. It can be seen from the responses of students that they are more motivated with Jigsaw and PBMP with a percentage of 70.6%. Learning management increased from the firstcycle to the second cycle. Positive activities undertaken students also increased from the first cycle to the second cycle.This study aims to determine the participation and motivation of the students, studentlearning outcomes and determine the quality of chemistry by combining Jigsaw model and PBMPpatterns on the material of Carbon Chemistry. This study is a Classroom Action Research held ontwo cycles. The subjects of this study were the students of class XII-IPA-2 SMAN 6 Madiun in theAcademic Year 2014-2015. The research design uses Classroom Action Research with two cycles,where each round consists of plans, activities and observation, reflection and revision of the draft.The methods of data collection is test data results, student activity sheets observation and datamanagement of learning. While the devices used are the Lesson Plan, Hand Out, and the StudentWorksheet. Data were analyzed descriptively. The results achieved in this study are: 1) The score ofeach test cycle shows that the application of a PBMP and Jigsaw model can improve studentsmastery learning. In the first cycle, the percentage of classical completeness is 70.59%. In thesecond cycle, the percentage of classical completeness is 85.29%. 2) The response of students inapplying PBMP patterns and Jigsaw model in the learning process carbon chemistry providespositive feedback. It can be seen from the responses of students that they are more motivated withJigsaw and PBMP with a percentage of 70.6%. Learning management increased from the firstcycle to the second cycle. Positive activities undertaken students also increased from the first cycleto the second cycle.